2013
DOI: 10.3109/14767058.2013.783810
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholestasis of pregnancy: new insights into its pathogenesis

Abstract: AbsractAim: To search a specific gene expression profile in women with intrahepatic cholestasis of pregnancy (ICP) and to evaluate the maternal and foetal outcome. Methods: We consecutively enrolled 12 women with ICP and 12 healthy pregnant controls. The gene expression profile was assayed with the microarray technique including a panel of 5541 human genes. Microarray data were validated by real-time PCR technique. Results: Caesarean delivery was performed in eight patients with ICP versus three controls (p ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…ICP has a complex etiology including genetic factors, endocrine factors, and the impact of pregnancy on FXR function (Abu-Hayyeh, Papacleovoulou & Williamson, 2013; Floreani et al, 2013). The present study focused on FXR-SHP regulation under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICP has a complex etiology including genetic factors, endocrine factors, and the impact of pregnancy on FXR function (Abu-Hayyeh, Papacleovoulou & Williamson, 2013; Floreani et al, 2013). The present study focused on FXR-SHP regulation under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of ICP are still not clear, but many studies have related this disease to abnormal bile acid metabolism (Abu-Hayyeh, Papacleovoulou & Williamson, 2013; Floreani et al, 2013). ICP with elevated bile acids in serum and liver is a major cause for premature embryo development and embryonic death (Diken, Usta & Nassar, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-related syndrome characterized by pruritus and elevated serum levels of liver enzymes and/or bile acids; the incidence varies geographically from 0.1 to 15.6% [1]. ICP is associated with increased risks of perinatal complications, including spontaneous preterm labor, fetal distress, and sudden intrauterine death [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the genes responsible for bile formation, including ACBC11 (bile salt export pump) and ABCB4 (MDR3), significantly increase a woman's chance of developing ICP, as well as other hepatobiliary diseases. Floreani et al () found that GABRA 2 was upregulated in ICP and this was involved in the pathophysiology of the pruritus experienced by women with this disorder.…”
Section: A Complex Disordermentioning
confidence: 99%